Techno-economic planning of distributed generation using modified whale optimization techniques - Raslan, Hussein Mahmoud; Osman, Zeinab Hanem; Hassan, Heba Ahmed (Alexandria engineering journal, 2025)
According to the no-free launch theorem for optimization, a particular technique does not normally fit to solve all types of optimization problems. Therefore, new optimization techniques need to be developed and already existing methods need to be updated. This paper presents two novel variants of the Whale Optimization (WOA) with multi-objective function, namely the Non-Dominated Sorting Whale Optimization Algorithm (NDSWOA) and the Enhanced Whale Optimization Algorithm (E-WOA). These algorithms are newly applied to the mixed integer nonlinear problem of optimal allocation and operating power factor selection of multiple, renewable, and grid connected distributed generation in radial electrical distribution networks. These algorithms aim to enhance the voltage stability and loadability multiplier, enhance the voltage profile, minimize power loss, and reduce the system total annual operating cost. Paper also addresses technical issue related to the operating power factor of different types of Renewable Energy Based Distributed Generation (REDG). A nose curve with voltage collapse point against system loading multiplier has been configured for all cases under study within this work for voltage stability evaluation. A binary version of the proposed algorithms is developed within this work to handle the discrete variables of the problem. The IEEE 33 and 69 buses systems are used as test cases to show the superiority of the introduced algorithms over the well-known WOA and other recently available techniques. This work relates the performance measurement indices to the total installed capacity of DG units to improve the economic objectives of power systems for the purpose of comparison with literature. For the IEEE 33-Bus system, three allocated PV stations using NDSWOA showed 93.59 %, 92.2 %, 93.71 % reduction in active and reactive power loss and total voltage deviation with 32.18 % increment in loading multiplier. While for the IEEE 69-Bus system, 97.978 %, 93.257 %, 94.407 %, and 43.049 % enhancement have been achieved respectively. The E-WOA shows almost the same results and enhancement percentages but with lower computational time which proves the advantages of the proposed techniques. [Display omitted]